The Effect Of Sila Ball Service Training Replaced On Takraw Service Ability - Elda Agung Darmawan (STKIP Muhammadiyah Kuningan, 2019)
This research is motivated by the ability of service or football in the game of sepak takraw, the students of State MTs are still low, with indications that the football is still easily accepted by opponents, the ball concerns the net or gets out of the field. The purpose of this study was to determine the effect of soccer soccer service training on the ability of the service to play football takraw for male students of class VIII. This research was an experimental study. The population in this study were male students of class VIII.A and VIII.B of State MTs Model Cigugur Kuningan, amounting to 30 students. The sampling technique used was total sampling by determining the population to be used as research samples to obtain male students of class VIII.A and VIII.B State MTs Model Cigugur Kuningan, amounting to 30 students. The data collection technique used is a service test on sepak takraw games. The data analysis technique in this study is the normality test and hypothesis test (z test) which is used to determine the effect of soccer soccer service training depending on service ability in football takraw VIII male students. Based on the statistical calculation obtained by Z Hit (10,037)> Z daf (2,35) then the hi received means that there is an effect on soccer soccer service training depending on service ability in football takraw VIII male students in the State Cigugur Kuningan MTs at the level of trust (α) 0.05 is acceptable. The conclusion of this study is that there is the effect of soccer soccer service training hanging on the ability of service in football takraw VIII male students.